A low complexity ZF precoding scheme based on weighted Gauss-Seidel in massive MIMO systems - Dong ZHOU; Haiyan CAO; Fangmin XU; Xin FANG; Xiumin WANG (Dianxin kexue, 2019)
In massive MIMO systems,due to inversion of Hermitian matrix,the complexity of the traditional ZF precoding method increases exponentially with increase of the number of users.To solve this problem,a low complexity digital ZF precoding scheme based on weighted Gauss-Seidel (WGS) was proposed.That was weighted addtion the iteration results of previous step and Gausee-Seidel iteration results to accelerate the iterative convergence.The weighting factor was determined by the least mean square sum,and the weighting factor was proved to make the algorithm converge.The simulation results show that the WGS algorithm can approximate the performance of ZF precoding scheme with very few iterations,and reduce the complexity of ZF precoding from O(K 3) to O(K2),where K is the number of users.